Aplikasi Kontroler PI Modifikasi pada Prototype Alat Pasteurisasi Menggunakan Simple Water Heater - Churnia Sari; Irna Tri; Asdi Putra (Jurnal Elektro dan Mesin Terapan, 2020)
PI controller is a control algorithm that was commonly used in industry because of its simplicity to be applied or simulated. In this case, the PI controller is used to regulate the temperature of the prototype of cow's milk pasteurization, which is designed using a Simple Water Heater. Pasteurization is a process of heating food with the aim of killing harmful organisms. Pasteurization is so influenced by the heating temperature. In this case, there is a component that has limited output performance. This component is commonly called the AC to AC Converter. It is used to control the temperature in the pasteurization plan or the others. To overcome this problem, a modification was needed, it is called Anti WindUp. So PI Controller was able to reach set point well, and has a very small steady-state error about 1%, more resistant to external disturbance and able to produce safe milk to consume.